HEAVY METAL LEVELS IN MEAT OF SPINY DOGFISH (SQUALUS ACANTHIAS) FROM BULGARIAN BLACK SEA - Veselin Kirov,; Hristina Neshovska; Iliyan Manev (Zenodo, 2022)
Environmental pollution with heavy metals and other toxic elements can serve as a predisposing factor for a various type of human diseases. Their accumulation in aquatic organisms used for human consumption increases the risk for daily intake of low doses of heavy metals. The Black Sea spiny dog (Squalus acanthias, Linnaeus 1758) is a cartilaginous fish predator belonging to the spiny shark family. This demersal fish belongs to the common monitoring species in Bulgaria and Romania in terms of pollution of the Black Sea. In this regard, the aim of the present study was to determine the concentrations of As, Pb, Cd, Hg, Mn, Zn and Al in shark meat samples, caught from our northern Black Sea coast (Varna region). The element with the highest concentration was arsenic. Mercury levels have been found to be above the permissible levels set out in Euro-pean and national legislation, which poses a potential health hazard risk for the consumers.